A Novel Erasure Coding Based on Reed Solomon Fault Tolerance for Cloud Based Storage (Global Journal of Computer Science and Technology, 2016)
In the recent years growth in usage of Erasure codes for fault tolerance is been observed The growth in distributed storage solutions is the root cause of this growth Multiple research is been carried out to propose the optimal fault tolerance solution for distributed storage solutions However the recent storage solutions have shown a migration towards to the cloud based storage solutions The growth of cloud computing and the benefits to the customer is the core of this migrations Thus the applications managing the storage solutions have also updated with the demand Hence the recent researches are driven by the demand of optimal fault tolerance solutions Here in this work we propose an optimal erasure code based fault tolerance solution specific for cloud storage solutions The work is been considered for commercial cloud based storage solution The final outcome of this work is improvement on Bit Error Rate for the proposed Novel Erasure Coding based on Reed Solomon Fault Tolerance for Cloud based service
Keywords: erasure; raid; raid 4; raid 5; array code; reed 2013; solomon code; azure; amazon s3